Bacillus velezensis - BIOCONTROL ACTIVITY OF MICROBIAL BIOMASS AND EXTRACELLULAR COMPOUNDS AGAINST Xanthomonas spp. - Pajčin, Ivana; Vlajkov, Vanja; Dodić, Jelena; Loc, Marta; Grahovac, Mila; Grahovac, Jovana (Journal on Processing and Energy in Agriculture, 2022)
Bacillus velezensis is a novel biocontrol species exhibiting several mechanisms in biological control of plant pathogens, including antibiosis, production of other types of antimicrobial compounds, such as volatile organic compounds, direct competition for nutrients and growth space, and induction of plant immunity towards pathogens. The aim of this study was to assess the potential of Bacillus velezensis IP22, grown on the optimized medium with glycerol as carbon source, for in vitro suppression of phytopathogenic Xanthomonas strains - Xanthomonas campestris and Xanthomonas euvesicatoria. Different potential biocontrol agents were investigated: the overall cultivation broth, containing biomass of Bacillus velezensis IP22 and produced extracellular metabolites, and biomass-free supernatant obtained by centrifugation of the cultivation broth (10000 rpm, 10 min), which contained only the produced extracellular compounds. Furthermore, supernatant samples were subjected to heat treatment to assess whether there were thermosensitive extracellular compounds present in the supernatant. Vacuum evaporation was performed to concentrate supernatant samples in order to compare the effect of higher concentration of extracellular compounds to pathogens’ growth. The results have indicated average inhibition zone diameters of 66.00 mm for the cultivation broth samples, 25.67 mm for the supernatant samples, 10.00 mm for the heat treated supernatant samples and 43.50 mm for the concentrated supernatant samples. Further research should include optimization of the production processes aimed at maximization of Bacillus velezensis IP22 biomass growth and/or biosynthesis of the antimicrobial metabolites, as well as their precise identification and characterization to better understand the mechanism(s) of biocontrol activity against phytopathogenic Xanthomonas spp.
Keywords: antimicrobial activity; cultivation broth; supernatant; heat treatment; Xanthomonas campestris; Xanthomonas euvesicatoria